Relationship of Sleep Quality and Health-Related Quality of Life in Adolescents According to Self- and Proxy Ratings: A Questionnaire Survey - Roeser, Karolin; Eichholz, Ruth; Schwerdtle, Barbara; Schlarb, Angelika A.; Kübler, Andrea (Frontiers in Psychiatry, 2012)
Introduction: Sleep disturbances are common in adolescents and adversely affect performance, social contact, and susceptibility to stress. We investigated the hypothesis of a relationship between sleep and health-related quality of life (HRQoL), and applied self- and proxy ratings. Materials and Methods: The sample comprised 92 adolescents aged 11–17 years. All participants and their parents completed a HRQoL measure and the Sleep Disturbance Scale for Children (SDSC). Children with SDSC T-scores above the normal range (above 60) were classified as poor sleepers. Results: According to self- and proxy ratings, good sleepers reported significantly higher HRQoL than poor sleepers. Sleep disturbances were significantly higher and HRQoL significantly lower in self- as compared to parental ratings. Parent-child agreement was higher for subscales measuring observable aspects. Girls experienced significantly stronger sleep disturbances and lower self-rated HRQoL than boys. Discussion: Our findings support the positive relationship of sleep and HRQoL. Furthermore, parents significantly underestimate sleep disturbances and overestimate HRQoL in their children.